Terapi Genggam Bola Karet Meningkatkan Kekuatan Otot Mendorong Pemulihan Pasca Stroke - Iq Balurrochman; Menik Kustriyani (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Stroke remains a primary etiology of persistent neurological disability, often manifesting as severe upper extremity motor deficits that critically restrict autonomous functioning. This empirical case study evaluated the clinical efficacy of a structured, nonpharmacological rubber ball gripping intervention on upper limb muscle strength dynamics among five post nonhemorrhagic stroke patients within a community health center framework. Employing a longitudinal pretest posttest design, baseline motor capacities were rigorously quantified utilizing the validated Manual Muscle Testing scale before undergoing a five day regimen of systematic mechanical stimulation. Comprehensive comparative matrix analysis revealed a uniform trajectory of motor recovery across all participants, characterized by an upward scale shift ranging from one to two functional tiers. Physiologically, the repetitive tactile and mechanical resistance induced by ball squeezing facilitated neuromuscular pathways, enhanced motor unit recruitment, and stimulated cortical neuroplasticity within the cerebral penumbra. These definitive clinical outcomes substantiate the therapeutic utility of simplified isometric exercises as an accessible, cost effective modality to rebuild motor architecture and enhance long term functional independencee.